2017
DOI: 10.1007/s40519-017-0374-0
|View full text |Cite
|
Sign up to set email alerts
|

Children with obesity: peer influence as a predictor of body dissatisfaction

Abstract: Peer influence predicted body dissatisfaction in children; however, children with obesity assimilate messages from their peers differently compared with children with normal weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…The present study investigated the role of weight-based teasing episodes in the classroom in relation to body dissatisfaction and eating restraint in middle childhood. Consistent with previous evidence, personal experiences of weight-based teasing were associated with body dissatisfaction (Amaya-Hernández et al, 2019; Jendrzyca & Warschburger, 2016; Juvonen et al, 2017; Kostanski & Gullone, 2007; Rosewall et al, 2018; Sinton et al, 2012), on the one hand, and eating restraint (Eddy et al, 2007; Gardner et al, 2000; Madowitz et al, 2012; Rosewall et al, 2018), on the other. Moreover, weight-based teasing experiences accounted for approximately 19% of the association between BMI and body dissatisfaction, and up to 35% of the link between BMI and eating restraint.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study investigated the role of weight-based teasing episodes in the classroom in relation to body dissatisfaction and eating restraint in middle childhood. Consistent with previous evidence, personal experiences of weight-based teasing were associated with body dissatisfaction (Amaya-Hernández et al, 2019; Jendrzyca & Warschburger, 2016; Juvonen et al, 2017; Kostanski & Gullone, 2007; Rosewall et al, 2018; Sinton et al, 2012), on the one hand, and eating restraint (Eddy et al, 2007; Gardner et al, 2000; Madowitz et al, 2012; Rosewall et al, 2018), on the other. Moreover, weight-based teasing experiences accounted for approximately 19% of the association between BMI and body dissatisfaction, and up to 35% of the link between BMI and eating restraint.…”
Section: Discussionsupporting
confidence: 88%
“…Weight-Based Teasing, Body Dissatisfaction, and Eating Restraint: Individual Level Associations Experiences of weight-based stigmatization are associated with body dissatisfaction among European Australian children (Kostanski & Gullone, 2007) and Latino preadolescent girls (Amaya-Hernández et al, 2019), while unhealthy weight control behavior (Madowitz et al, 2012), eating pathology (Eddy et al, 2007), and weight gain (Juvonen et al, 2017) are found to be related to weight-based teasing among American children. In addition, weight-based teasing prospectively predicts body image concerns and mediates the relation between body weight and body dissatisfaction among pre-and early American adolescents (Sinton et al, 2012).…”
Section: Body Dissatisfaction and Eating Restraint In Middle Childhoodmentioning
confidence: 99%
“…These results suggest that body dissatisfaction and self-esteem are not only associated during adolescence [e.g., 32] but body dissatisfaction may also have a negative impact on young children' developing self-esteem [17]. Third, children's body dissatisfaction was associated with perceptions of their peers' body dissatisfaction [15,16], suggesting that peers may be significant sources of influence on body satisfaction not only in early adolescence [e.g., 51,52] and adolescence [e.g., 53], but also in preschoolers [15,16]. Fourth, only three studies have analyzed the relationships between body dissatisfaction and diet in preschool children.…”
Section: Body Image and Relationships With Bmi Self-esteem Peer's Bmentioning
confidence: 93%
“…The sample size was calculated by using OpenEpi online software, version 3.01. Considering 67% of prevalence of BID in obese children, 26 at 95% CI (1−α), power as 80%, ratio of controls to cases as 1, the proportion of controls with exposure as 45, and proportion of cases with exposure as 67, the total required sample was 176. Considering a 10% dropout rate, the sample size was rounded off to 100 each in the obese group and the control group (normal weight).…”
Section: Methodsmentioning
confidence: 99%